The effect of financial literacy, financial attitudes and income on financial management behavior at PT Beton Perkasa Wijaksana - Riesty Andella; Herayati; Martinus Wahyu Purnomo (Institute of Computer Science (IOCS), 2023)
Many people think in the short term, so operational financial management becomes very important. It is very important for the financial management of an organization or individual, especially in the industrial sector, to ensure ongoing operations and achieve long-term financial goals. This research is a quantitative descriptive research that uses survey methods to collect data from panels or respondents. In this sampling, probability sampling is used. Therefore, this study involved 40 employees of PT Beton Perkasa Wijaksana. In this study, quantitative analysis, classical assumption test, t and F test, and the results of the regression equation were used. Based on the results of multiple linear regression, it can be concluded that the income variable has a greater coefficient value than the Financial Literacy and Financial Attitude variables. Based on the simultaneous results, with Ftable 2.86 and Fcount 23.717, it can be concluded that Financial Literacy, Financial Attitudes, and Income have a significant and positive influence on financial management behavior.